The Use of Montessori Learning Media in Introducing Number Symbol Concepts to Children Aged 4-5: (Classroom Action Research at Marie Joseph Kindergarten, Jakarta) - Puspitasari, Putri Ratih; Irwansyah, Asep; Sopiah; Ericka (LPPM Universitas Mohammad Husni Thamrin, 2025)
One of the educational games (APE) that supports learning activities to recognize the concept of numbers for early childhood is the Montessori concept game. Known as an educational game tool because this Montessori-created game is a medium that can make it easier for children to count. The results of initial observations of the lack of teacher socialization at Marie Joseph Kindergarten related to the use of Montessori math game tools. This study aims to describe the use and benefits of learning media of montessori in recognizing number symbols in children aged 4-5 years. This research method uses a qualitative approach. Analysis techniques with data reduction, data display and data verification. Based on data from observations, interviews and data triangulation, there is an increase in the ability to recognize number symbols in children aged 4-5 years, through providing actions through the Montessori method. This can be seen from the increase in each indicator, namely being able to count sequentially from numbers 1-10, recognizing number symbols 1-10, being able to write number symbols 1-10. The Montessori method can improve the ability to recognize number symbols to children in a concrete way first, then abstractly. The introduction of number symbols through the Montessori method can enhance children's cognitive development in recognizing number symbols in children aged 4-5 years. Therefore, this study concludes that the Montessori method can improve the number symbol recognition skills of children aged 4-5 years at Marie Joseph Kindergarten.